2008
DOI: 10.1093/cvr/cvn088
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic hyperparathyroidism causes a reversible inflammatory process of aortic valve calcification in rats

Abstract: AimsRenal failure is associated with aortic valve calcification (AVC). Our aim was to develop an animal model for exploring the pathophysiology and reversibility of AVC, utilizing rats with diet-induced kidney disease.Methods and resultsSprague–Dawley rats (n = 23) were fed a phosphate-enriched, uraemia-inducing diet for 7 weeks followed by a normal diet for 2 weeks (‘diet group’). These rats were compared with normal controls (n = 10) and with uraemic controls fed with phosphate-depleted diet (‘low-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
4
25
1
Order By: Relevance
“…This unique model is based on the development of transient uremia-induced secondary hyperparathyroidism and represents the metabolic and hormonal changes occurring in calcification secondary to RF. Interestingly, AVC almost completely regressed after RF resolution and normalization of metabolic abnormalities, implying, for the first time, that AVC might be a reversible process (31). Similar results have been shown in a mouse model using a hypercholesterolemic animal model of aortic valve disease (21).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…This unique model is based on the development of transient uremia-induced secondary hyperparathyroidism and represents the metabolic and hormonal changes occurring in calcification secondary to RF. Interestingly, AVC almost completely regressed after RF resolution and normalization of metabolic abnormalities, implying, for the first time, that AVC might be a reversible process (31). Similar results have been shown in a mouse model using a hypercholesterolemic animal model of aortic valve disease (21).…”
supporting
confidence: 77%
“…The decline in apoptosis might be explained by a reduction in the inflammatory process bringing up a new equilibrium in cell apoptosis and renewal. The reversibility of calcification was recently confirmed in an additional model of AVC based on high LDL-cholesterol levels (21,31). The authors of that study demonstrated that rapid normalization of cholesterol levels in mice resulted in a regression of AVC.…”
Section: Apoptosis and Related Pathways In Avcmentioning
confidence: 83%
See 2 more Smart Citations
“…35 In contrast, reversal of aortic valve calcification in uremic rats was shown after removal of adenine and supplemental phosphate from the diet. 36 The mechanism of the calcium resorption was not investigated.…”
Section: Discussionmentioning
confidence: 99%